Adolescent Obesity Prevention in Saudi Arabia: Co-identifying Actionable Priorities for Interventions - Almughamisi, Manal; O'Keeffe, Majella; Harding, Seeromanie (Frontiers in Public Health, 2022)
Background Childhood obesity is a serious issue in the Kingdom of Saudi Arabia, but there is no known community intervention. The aim of the study was to use a participatory approach to obtain the perspectives of students, school staff and Ministry of Education (MoE) representatives and parents on important and feasible intervention opportunities for school-based obesity prevention for adolescent girls. Method The study was conducted in two intermediate schools for girls (13–15 years old) in Jeddah that were purposefully identified with the support of the MoE. Group concept mapping, a mixed method approach, was conducted with 19 adults which included staff from the MoE and schools, school canteen suppliers and mothers. Adults generated statements in response to two prompts (P); P1 “The factors influencing adolescent obesity in Saudi are...” and P2 “The content of school-based programmes should focus on....” Photovoice-enhanced concept mapping was used with students (n = 15 students) to capture adolescent perspectives on what influences their dietary and physical activity habits. Students generated statements' using their own photographs. Stakeholders, both adult and students, sorted the statements into themes and rated each statement for relative importance and feasibility. Multidimensional scaling and hierarchical cluster analyses were used to produce concept maps with the input from students and adults. Result Adults generated 35 statements in response to P1 and identified five themes that influenced adolescent obesity including “Home Environment,” “Lifestyle,” “School Environment,” “Community,” “Biology.” They generated 42 statements in relation to P2 and identified four themes including “Ministry of Education Support,” “School Environment,” “Public health programmes” and “Wider environmental influences.” Students generated 42 statements from 39 pictures. They identified five themes that influenced their dietary and physical activity habits—“Role of Government,” “School Environment,” “Home Environment,” “Retail Environment” and “Cultural Practices.” Both groups identified several common important and feasible actions with a strong emphasis on improving the school environment, in particular food provision, with MoE support. Exemplar corresponding statements from adults were “Offer healthy foods in the canteen,” “Remove chocolates and sweets” and “Educate children about healthy foods” and from students were “Offer fruit and vegetables in the canteen,” “Remove chocolates from the canteen,” “Healthy meals should not expensive.” Lack of correspondence related to students' emphasis on access to both healthy foods and physical activity in schools and the wider environment (e.g. retail environments), while adults emphasized school-based education and food provision. After further consultations, both stakeholder groups agreed on improving access to healthy foods in the canteen. Conclusions Students and school and MoE staff jointly agreed that a canteen-based intervention was important and feasible to improve dietary habits and thus help to prevent obesity among adolescent girls. This was the first time a participatory approach was used with students for intervention development in Saudi Arabia. A co-development approach may have value to improve their school food environments.